L’efficacité de l’utilisation de chansons populaires comme le média d’apprentissage de la prononciation du français pour les étudiants du premier semestre de l’Université Negeri Semarang - Fareeha Ali; Neli Purwani (Universitas Negeri Semarang, 2024)
Foreign languages, including French, are taught in secondary schools and universities. In French, there are four basic language skills, namely Reading Comprehension (reading), Listening Comprehension (listening), Speaking Production (speaking), and Writing Production (writing). Of these four skills, foreign language learners are sometimes faced with problems of imprecise pronunciation. Therefore, there is a need for media that can help students in the process of learning French pronunciation, particularly the use of audio media in the form of popular French songs. Thus, this research aimed to demonstrate the effectiveness of using popular French songs in teaching pronunciation to university students. The method used was the pre-experimental design of a pre-test and post-test in a group consisting of first giving a pre-test to 19 respondents, then a treatment was carried out, after which a post-test was administered. The results of this research show an increase in students' pronunciation abilities, so popular French songs are used effectively as a medium for learning pronunciation among students.